Subsidized Small Jobs and Maternal Labor Market Outcomes in the Long Run - Matthias Collischon; Kamila Cygan-Rehm; Regina T. Riphahn (CESifo GmbH, 2024)
This paper investigates whether incentives generated by public policies contribute to motherhood penalties. Specifically, we study the consequences of subsidized small jobs, the German Minijobs, which are frequently taken up by first-time mothers upon labor market return. Using a combination of propensity score matching and an event study applied to administrative data, we compare the long-run child penalties of mothers who started out in a Minijob employment versus unsubsidized employment or non-employment after birth. We find persistent differences between the Minijobbers and otherwise employed mothers up to 10 years after the first birth, which suggests adverse unintended consequences of the small jobs subsidy program for maternal earnings and pensions.
Keywords: J22; J13; J18; 330; motherhood penalty; small job subsidies; Minijobs; maternal employment; labor market policy; propensity score matching